Feruloylation and structure of arabinoxylan in wheat endosperm cell walls from RNAi lines with suppression of genes responsible for backbone synthesis and decoration. Issue 11 (21st April 2017) - Freeman, Jackie; Ward, Jane L.; Kosik, Ondrej; Lovegrove, Alison; Wilkinson, Mark D.; Shewry, Peter R.; Mitchell, Rowan A.C.
Summary: Arabinoxylan (AX) is the major component of the cell walls of wheat grain (70% in starchy endosperm), is an important determinant of end‐use qualities affecting food processing, use for animal feed and distilling and is a major source of dietary fibre in the human diet. AX is a heterogeneous polysaccharide composed of fractions which can be sequentially extracted by water (WE‐AX), then xylanase action (XE‐AX) leaving an unextractable (XU‐AX) fraction. We determined arabinosylation and feruloylation of AX in these fractions in both wild‐type wheat and RNAi lines with decreased AX content (TaGT43_2 RNAi, TaGT47_2 RNAi) or decreased arabinose 3‐linked to mono‐substituted xylose (TaXAT1 RNAi). We show that these fractions are characterized by the degree of feruloylation of AX, <5, 5–7 and 13–19 mg bound ferulate (g −1 AX), and their content of diferulates (diFA), <0.3, 1–1.7 and 4–5 mg (g −1 AX), for the WE, XE and XU fractions, respectively, in all RNAi lines and their control lines. The amount of AX and its degree of arabinosylation and feruloylation were less affected by RNAi transgenes in the XE‐AX fraction than in the WE‐AX fraction and largely unaffected in the XU‐AX fraction. As the majority of diFA is associated with the XU‐AX fraction, there was only a small effect (TaGT43_2 RNAi, TaGT47_2 RNAi) or no effect (TaXAT1 RNAi) on total diFA content. Our results are compatible with a model where, to maintain cell wall function, diFA is maintained at stable levels when other AX properties are altered.